REFLECTION OF NATIONAL IDENTITY AND NEW HISTORICISM IN THE WORKS OF SUDHA MURTHY - Tonikabe Devi, Ningombam; Singh, Mutum Rameshwor (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian children’s literature has a prolonged history of rich traditions and oral storytelling, filled with myths and folklore. Sudha Murthy’s simple yet relatable storytelling is drawn mostly from her real-life experience spicing it up with Indian folklore. She integrates cultural heritage with modern relevance and helps young readers understand their roots. By drawing on New Historicist strategies - like reading the text alongside its historical background, examining the text’s engagement with dominant cultural ideologies, and examining the operation of power and identity through storytelling - children’s literature can be viewed in a new light and not just as innocent or neutral storytelling. This paper examines Sudha Murthy’s contribution to children’s literature and their role in constructing national identity from a New Historicist perspective. Her use of different symbolic tools to portray the Indian rural culture and the traditions followed and practised by the people can be seen throughout her work.